PERAN KELUARGA DALAM PENGAMBILAN KEPUTUSAN IBU NIFAS UNTUK MELAKUKAN PRAKTIK PANTANG MAKANAN DI KOTA PEKALONGAN - Indar Widowati; Afiyah Sri Harnany; Zaenal Amirudin (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2016)
BACKGROUND: ABSTINENCE FROM FOOD IS AN INDIVIDUAL BEHAVIOR TO NOT EAT CERTAIN FOODS BECAUSE THERE IS A BAN BESIFAT OBTAINED CULTURE FOR GENERATIONS. STILL THE PUERPERAL WOMEN WHO ABSTAIN FROM CERTAIN FOODS LIKELY INFLUENCED BY SEVERAL FACTORS INCLUDING THE ROLE OF THE FAMILY.THE PURPOSE OF THIS STUDY WAS TO EXPLORE THE ROLE OF THE FAMILY IN THE DECISIONMAKING POSTPARTUM MOTHERS TO PRACTICE ABSTINENCE FEEDING ON POSTPARTUM MOTHERS. THIS RESEARCH IS A QUALITATIVE DESCRIPTIVE STUDY, TAKING PARTICIPANTS WITH METHODS PURPUSIVE SAMPLING, PARTICIPANTS WERE FOUR POSTPARTUM MOTHERS WHO DO ABSTAIN FROM EATING, WHILE TRIANGULATION COMPOSED OF TWO POSTPARTUM MOTHERS WHO DO NOT ABSTAIN FROM FOOD, TWO MOTHERS OR MOTHERS-IN-LAW POSTPARTUM MOTHERS WHO ABSTAIN FROM FOOD, TWO PEOPLE MOTHER OR MOTHER-IN-LAW POSTPARTUM MOTHERS WHO DO NOT ABSTAIN FROM FOOD, ONE MIDWIFE AND ONE MIDWIFE. DATA IS COLLECTED USING IN-DEPTH INTERVIEWS, DATA IS PROCESSED BY THE METHOD OF INDUCTION.THE RESULTS SHOWED THAT THE PRACTICE OF ABSTINENCE FEEDING ON POSTPARTUM MOTHER INFLUENCED BY FAMILY MEMBERS WHO LIVE WITH THE PARTICIPANTS, ESPECIALLY THE BIRTH MOTHER OR MOTHER-IN-LAW, WHILE THE HUSBAND OF THE PARTICIPANTS DID NOT HAVE A SIGNIFICANT ROLE IN THE PRACTICE OF ABSTINENCE EAT. CONCLUSION PRACTICE ABSTINENCE FROM FOOD ON POSTPARTUM MOTHER INFLUENCED BY THE ROLE OF THE FAMILY, ESPECIALLY THE MOTHER OR MOTHER-IN-LAW.